Redescription of an enigmatic salamander, Pseudohynobius puxiongensis (Fei et Ye, 2000) (Urodela: Hynobiidae) - Xiong, Jian-Li; Gu, Hai-Jun; Gong, Tian-Jian; Zeng, Xiao-Mao (Zootaxa, 2011)
Protohynobius puxiongensis Fei et Ye, 2000, a poorly known hynobiid, was described from a single specimen. The new genus was erected because of its peculiar internasal bone. Recent molecular investigations transferred the species to genus Pseudohynobius and presence of the internasal bone was shown to be a variable character. Taxonomically this species is relatively poorly known with no descriptions of egg, larvae, habitat, and other biological data. Furthermore, the extent of adult variation is unknown. We describe features of the adult, larvae, egg sacs, karyotype, breeding habitat and habits. The species is characterized by the following features: dorsal color gray-yellow with yellowish spots; dorsal tail with distinct yellowish line; total length shortest in the genus; tail length shorter than snout-vent length; head length to head width ratio smaller than 1.53; and a moderate number of vomerine teeth (11–15). The karyotype and the breeding season of Ps. puxiongensis are similar to that of other species of the genus.